Revitalizing Elementary Education: The Impact of Characteristic Learning Development and P5 Implementation on Mitigating Learning Loss - Sri Dewi Nirmala; Tita Rosita; Wakhudin Wakhudin; Sendi Ramdhani; Riandi Marisa (STAI Hubbulwathan Duri, 2024)
This study analyzes strategies to reconstruct learning experiences in elementary schools, focusing on character development and the Pancasila Student Profile Strengthening Project (P5) to mitigate learning loss. Conducted in Bogor, Jakarta, and Banyumas, this research used a phenomenological approach to explore participants' lived experiences, aligning with the study’s focus on personal insights into learning loss impacts. Purposive sampling selected participants, including teachers, principals, and two students from each of five schools, chosen for their direct engagement in character education and P5 activities. Data were collected via interviews, observations, and documentation, with credibility validated through triangulation. Findings reveal that learning loss impacts are significant and multifaceted, including declines in motivation, increased learning disparities, dropout risks, delays in reading, and decreases in academic performance and character. Effective character development was identified as involving positive reinforcement, a character-centered school culture, teacher modeling, and habitual practices. The P5 project, implemented through a project-based learning model, effectively integrated Pancasila values, fostering essential character traits such as perseverance, hard work, and adaptability alongside academic skills. The results highlight the P5 project's role in addressing learning loss by enhancing both academic and character growth. This approach provides practical insights for schools aiming to strengthen student resilience and adaptability. The study concludes that character development and P5 implementation can effectively reconstruct learning experiences in elementary education, supporting both academic recovery and character formation. These findings offer implications for educators and policymakers seeking comprehensive strategies to address learning loss in Indonesian schools.